2013
DOI: 10.1371/journal.pone.0061687
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Effects of Ganoderma Lucidum Spores on Epileptiform Discharge Hippocampal Neurons and Expression of Neurotrophin-4 and N-Cadherin

Abstract: Epilepsy can cause cerebral transient dysfunctions. Ganoderma lucidum spores (GLS), a traditional Chinese medicinal herb, has shown some antiepileptic effects in our previous studies. This was the first study of the effects of GLS on cultured primary hippocampal neurons, treated with Mg2+ free medium. This in vitro model of epileptiform discharge hippocampal neurons allowed us to investigate the anti-epileptic effects and mechanism of GLS activity. Primary hippocampal neurons from <1 day old rats were cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…To determine the percentage of neurons present, hippocampal neurons in culture were labeled by immunofluorescence staining, according to previous protocols [30]. Briefly, the neurons were cultured for 5 days, and the cultures were fixed with 4% paraformaldehyde for 15 min and were incubated with the neuron-specific primary antibody against neuron-specific enolase (NSE) (Abcam, Cambridge‚UK; 1:200) overnight and finally with an appropriate fluorophore-tagged secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the percentage of neurons present, hippocampal neurons in culture were labeled by immunofluorescence staining, according to previous protocols [30]. Briefly, the neurons were cultured for 5 days, and the cultures were fixed with 4% paraformaldehyde for 15 min and were incubated with the neuron-specific primary antibody against neuron-specific enolase (NSE) (Abcam, Cambridge‚UK; 1:200) overnight and finally with an appropriate fluorophore-tagged secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…The spores of Ganoderma lucidum (SGL), ejected from the pileus of G. lucidum in the mature phase, are tiny and mist-like particles of about 6.5–8.0 × 9.6–12.6 μm enwrapped with an outer bilayer of sporoderm [12]. During the past two decades, because the spores could be collected on a large scale, SGL has attracted extensive interest as studies revealed that the spores possess many bioactive substances, including polysaccharides, unsaturated fatty acids, triterpenoids, nucleotides, ergostero and other bioactive ingredients [13,14]. In vitro, the polysaccharides of SGL had strong bioactivity in scavenging 1,1-Diphenyl-2-picrylhydrazyl and oxygen radicals [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the search for an alternative epilepsy therapy, Ganoderma Lucidum Spore Powder (GLSP) is a potential intriguing candidate. [ 11 14 ] It has been reported that animal data have supported that the antiepileptic effect of GLSP in both in vivo and in vitro studies. [ 11 – 24 ] Presently, limited data of using GLSP in treating human epilepsy is available.…”
Section: Introductionmentioning
confidence: 99%